Perancangan Sistem Identifikasi Tipe Sidik Jari Manusia Menggunakan Matlab - Fitri Rahmah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
Human fingerprints are unique in this world. This is why human fingerprints are frequently used as a form of identification or self-recognition. Human fingerprints are classified into three categories: whorl, arch, and loop. The wavelet transformation is used because it is capable of identifying discontinuous lines. Because human fingerprints contain discontinuous lines, this method is ideal for recognizing fingerprint images, which are then compared to database images. Additionally, the method of image processing with Matlab software and integration with a GUI (Graphical User Interface) is described, so that it can be used to recognize human fingerprint types.